The Role of Men in Islamic Society: Analysis of the Roles and Responsibilities of Men in Islamic Society - Hendio Anjasmara; Budi Afriandi; Hengki Ras Bumi; Eliyadi Eliyadi; Thiago Rocha (Yayasan Adra Karima Hubbi, 2025)
Gender discourse in Islam has tended to focus on women's issues, while comprehensive analysis of men's roles and responsibilities is still limited. This study aims to examine how men's roles are constructed, interpreted, and transformed in the context of contemporary Islamic society. The research methodology uses textual analysis of primary Islamic sources, as well as a literature review of current research on gender and Islam. The results of the study indicate that Islam establishes the position of men based on the principle of spiritual equality with women, but provides a special role in family and community leadership. The concept of male qawwamah (leadership) in the family is interpreted not as patriarchal domination, but as a mandate that demands material and spiritual responsibility. In the public sphere, men have a strategic role in political, social, and religious leadership with the principles of deliberation and justice. Contemporary social transformations, including urbanization and increasing participation of women in education and the economy, according to a more flexible reinterpretation of gender roles without sacrificing fundamental Islamic values. This study recommends the development of further interdisciplinary studies on gender dynamics in contemporary Muslim societies to support the creation of a gender-just society based on Islamic values.